Increased susceptibility to Mycobacterium avium in hemochromatosis protein HFE-deficient mice - Sandra Gomes Pereira (2008)
Mycobacterium avium is an opportunistic infectious agent in immunocompromised patients, living inside macrophage phagosomes. As for other mycobacterial species, iron availability is a critical factor for M. avium survival and multiplication. Indeed, an association between host secondary iron overload and increased susceptibility to these mycobacteria is generally acknowledged. However, studies on the impact of primary iron overload on M. avium infection have not been performed. In this work, we used animal models of primary iron overload that mimic the human disease hereditary hemochromatosis. This pathology is characterized by increased serum transferrin saturation with iron deposition in parenchymal cells, mainly in the liver, and is most often associated with mutations in the gene encoding the molecule HFE. In this paper, we demonstrate that mice of two genetically determined primary iron overload phenotypes, Hfe(-/-) and beta 2m(-/-), show an increased susceptibility to experimental infection with M. avium and that during infection these animals accumulate iron inside granuloma macrophages. beta 2m(-/-) mice were found to be more susceptible than Hfe(-/-) mice, but depleting Hfe(-/-) mice of CD8(+) cells had no effect on resistance to infection. Overall, our results suggest that serum iron, rather than total liver iron, levels have a considerable impact on susceptibility to M. avium infection.